2005
DOI: 10.1017/s0012162205001039
|View full text |Cite
|
Sign up to set email alerts
|

Explicit memory performance in infants of diabetic mothers at 1 year of age

Abstract: The aim of the present research was to investigate the impact of abnormal fetal environment on explicit memory performance. Based on animal models, it was hypothesized that infants of diabetic mothers (IDMs) experience perturbations in memory performance due to exposure to multiple neurologic risk factors including: chronic hypoxia, hyperglycemia/reactive hypoglycemia, and iron deficiency. Memory performance, as measured by the elicited/deferred imitation paradigm, was compared between 13 IDMs (seven females, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(73 citation statements)
references
References 30 publications
2
70
1
Order By: Relevance
“…However, 2 studies 35,36 were further excluded because they were published with the same populations used in 2 included studies. 18,20 In addition, 5 relatively different studies 22,32,[37][38][39] were conducted by using the same cohort study with varied sample sizes. All reported global cognitive development as a secondary outcome or confounder at the age of 1 year 32, 37-39 and 4 years.…”
Section: Resultsmentioning
confidence: 99%
“…However, 2 studies 35,36 were further excluded because they were published with the same populations used in 2 included studies. 18,20 In addition, 5 relatively different studies 22,32,[37][38][39] were conducted by using the same cohort study with varied sample sizes. All reported global cognitive development as a secondary outcome or confounder at the age of 1 year 32, 37-39 and 4 years.…”
Section: Resultsmentioning
confidence: 99%
“…Patients with "developmental amnesia", who incurred hippocampal damage early in life, also exhibit impairments on the deferred imitation task, although their impairment is restricted to the recall of the temporal order of actions (Adlam, Vargha-Khadem, Mishkin, & de Haan, 2005). Infants who are at risk for damage to the medial temporal lobe memory system because of adverse fetal environments, also exhibit impairments in recalling the temporal order of imitation sequences (DeBoer, Wewerka, Bauer, Georgieff, & Nelson, 2005).…”
Section: Deferred Imitationmentioning
confidence: 99%
“…11,12 Dionne et al 13 reported significant expressive language impairments in young children born to mothers with gestational diabetes (GDM) compared with children of women without diabetes. Moreover, 2 small studies 14,15 demonstrated mild deficits in recognition memory performance in infants of mothers with diabetes, suggesting aberrations in hippocampal function. Abnormalities within the limbic system have also been documented in children with ASD, and language deficits are among the core features of this disorder.…”
mentioning
confidence: 99%